Molecular characterization of geminivirus causing yellow vein mosaic in pumpkin - Sahna Hamsa N H (Centre for Plant Biotechnology and Molecular Biology, College of Horticulture, 2011)
The study entitled “Molecular characterization of geminivirus causing yellow vein mosaic in pumpkin (Cucurbita moschata Duch. Ex poir.)” was carried out in the Molecular Biology Laboratory of Centre for Plant Biotechnology and Molecular Biology, College of Horticulture, Vellanikkara during the period 2009-2011. The objectives of the study included the molecular characterization of geminivirus causing yellow vein mosaic disease in pumpkin and developing a PCR based diagnostic kit. Yellow vein mosaic infected pumpkin leaf sample was collected from the field of Olericulture Department, College of Horticulture, Vellanikkara and total genomic DNA was extracted by CTAB method. Specific primers for coat protein and movement protein genes were designed based on the sequences of geminiviruses infecting vegetables, obtained from the NCBI database. PCR amplification was carried out using these primers. Amplicons of size ~900bp and ~700bp were obtained for coat protein and movement protein genes respectively. The purified PCR products were ligated in pGEMT plasmid vector and cloned. The recombinant E. coli cells were selected based on blue white screening on LB agar containing ampicillin layered with X-gal and IPTG. After confirmation of the inserts by colony PCR, the clones were sequenced. Sequences of 891bp and 702 bp were obtained for coat protein and movement protein genes respectively. Sequence analysis was carried out with standard bioinformatics tools. On blastn analysis both coat protein and movement protein sequences showed maximum similarity to Squash leaf curl China virus (SLCCV) from Coimbatore. For coat protein gene, full length ORF of 771bp was obtained and the ORF of movement protein was partial. Primers MP1F and MP1R with expected amplicon size of 1363bp were designed to get full length ORF (846bp) of movement protein gene. The technique was validated with DNA from 15 PYVM infected and 4 healthy pumpkin leaf samples collected from Palakkad, Thrissur and Malappuaram districts. The virus was detected only in the diseased samples. Hence these primers could be used in developing a molecular diagnostic tool to detect the virus. PCR amplifications were carried out in weed plants like Emilia sonchifolia, Ageratum conyzoides, Hibiscus surattensis and Synedrella nodiflora and crop plants like okra and ash gourd with yellow vein symptom to check whether these plants serve as the collateral hosts of the virus. PCR amplification was also performed in bitter gourd with distortion mosaic symptom. No amplifications were obtained in plants other than pumpkin. Using the primers PYVMV was detected in apparently healthy mature leaves of infected pumpkin. Hence, these primers could be used to detect latent infection. Sequence and phylogenetic analysis of coat protein and movement protein gene sequences showed maximum similarity to bipartite Squash leaf curl china virus (SLCCV) from Coimbatore. Hence Pumpkin yellow vein mosaic virus (PYVMV) from Kerala can be considered as a strain of SLCCV.